An ergonomics study on the evaluation of carpal tunnel syndrome among Chikan embroidery workers of West Bengal, India. (September 2015) - Gangopadhyay, Somnath; Chakrabarty, Sabarni; Sarkar, Krishnendu; Dev, Samrat; Das, Tamal; Banerjee, Sunetra
Abstract : Background: Chikan embroidery is a popular handicraft in India that involves hand-intensive stitching while seated in a static posture with the upper back curved and the head bent over the fabric. Women perform most Chikan embroidery. Objectives: The aim of this study was to analyze the repetitive nature of this work among female Chikan embroiderers by measuring the prevalence of upper extremity discomfort and carpal tunnel syndrome (CTS). Methods: The Nordic musculoskeletal questionnaire was used to analyze the extent of upper extremity pain symptomology. The repetitive nature of Chikan embroidery work was evaluated using the Assessment of Repetitive Tasks of the upper limbs tool (ART). Motor nerve conduction studies of median and ulnar nerves were performed with embroidery workers and a control group to determine the risk of CTS. Results: Among embroidery workers, the prevalence of wrist pain was 68% and forearm pain was 60%. The embroiderers also commonly reported Tingling and numbness in the hands and fingertips. The ART analysis found that Chikan embroidery is a highly repetitive task and nerve conduction studies showed that the embroidery workers were more likely to experience CTS than women in the control group. Conclusions: Chikan embroidery is a hand-intensive occupation involving repetitive use of hands and wrists and this study population is at risk of experiencing CTS. Future research should explore the potential benefits of ergonomics measures including incorporating breaks, stretching exercises, and the use of wrist splints to reduce repetitive strain and the probability of developing CTS.